2018
DOI: 10.1111/trf.15045
|View full text |Cite
|
Sign up to set email alerts
|

High rate of seromarkers for HIV, HBV and syphilis among blood donors using confidential unit exclusion, before and after HIV‐NAT implementation at a major public blood bank in the Brazilian Amazon

Abstract: BACKGROUND: Confidential unit exclusion (CUE) was introduced in the 1980's as an additional layer to blood safety, before highly specific and sensitive nucleic acid tests (NAT) for HIV were implemented. The utility of CUE-use in settings that have implemented NAT should be evaluated over time. STUDY DESIGN, METHODS: Cross-sectionalretrospective study carried out from June 2010-November 2015, at Manaus Hemocenter (HEMOAM), Amazonas, Brazil that implemented HIV-NAT in 2012. The HIV, HCV, HBV, HTLV, Chagas diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…In the Amazon region, the estimated prevalence of HCV infection ranges from 1% to 3%, with higher rates being recorded in vulnerable groups, such as PWUDs (23.1%), patients undergoing hemodialysis (8.4%), and patients with hemophilia (48.4%) [5,[20][21][22][23][24]29,36,46]. The prevalence of HCV infection detected in this study was 10.7%, and most of these infections were classified as active (7.8%).…”
Section: Discussionmentioning
confidence: 67%
“…In the Amazon region, the estimated prevalence of HCV infection ranges from 1% to 3%, with higher rates being recorded in vulnerable groups, such as PWUDs (23.1%), patients undergoing hemodialysis (8.4%), and patients with hemophilia (48.4%) [5,[20][21][22][23][24]29,36,46]. The prevalence of HCV infection detected in this study was 10.7%, and most of these infections were classified as active (7.8%).…”
Section: Discussionmentioning
confidence: 67%
“…Previous reports from HEMOAM, a reference public blood bank in Amazonas state, Northern Brazil, showed a significant number of HIV‐1 infections in blood donors and a remarkable prevalence of Subtype B (M.E. Crispim et al, submitted for publication) . In this study we describe TDR/DRM rate and transmission clusters of drug‐resistant viruses in these HIV‐positive ARV‐naive blood donors from Northern Brazil.…”
mentioning
confidence: 61%
“…Crispim et al, submitted for publication). 18,19 In this study we describe TDR/DRM rate and transmission clusters of drug-resistant viruses in these HIV-positive ARV-naive blood donors from Northern Brazil.…”
mentioning
confidence: 99%
“…In relation to HIV, 20 cases were detected by NAT, and in relation to HCV, 61 cases detected by NAT were reported. In a public blood bank in the Brazilian Amazon (HEMOAM), Souza et al (2019) found that most donations (73.4%) were positive for HIV–NAT, with 4 donations in the diagnostic window period.…”
Section: Discussionmentioning
confidence: 99%